(untitled) (International Journal of Physiotherapy, 2016)
Background: Adhesive capsulitis (AC) of shoulder is a common condition encountered by physical therapists in their routine outpatient care services; AC of shoulder is as by itself being a self limiting disorder lasts from months to years causing pain and discomfort to the patients. The condition is commonly associated with Diabetes mellitus or other co morbidities. The incidence of AC is high among diabetic individuals and it becomes mandatory on the part of physical therapists and other health professionals to approach this issue on a holistic manner. This paper deals with the importance of a physiotherapist role in prevention and dealing with the causative factors of AC and not merely its symptom. Methods: Extensive literature review was done from the electronic data bases, Systematic reviews and critical reviews from Pub med indexed journals and other peer reviewed publications across the globe. Results: It was not the type of diabetes but the duration of the disease and the glycemic index, marking the causative factor for adhesive capsulitis of shoulder. Conclusion: It may be concluded that physiotherapist play a vital role in identifying the pre-diabetic or a diabetic state of an individual reporting in a multi disciplinary set up with a AC of shoulder, and also has a role in the prevention of AC by helping the individual to maintain a good glycemic control with a holistic approach which includes aerobic exercises, General Flexibility exercises, Weight management and Yoga therapy.